Sosialisasi Pembuatan Pupuk Organik Cair (POC) di Desa Perian Lombok Timur - Safitri, Arni Raudina; Fardiaz, M. Abdurrahman; Firmanu, Zulhan Ozi; Cahya, Eka Adithya Altri; Saputra, Armadani; Rusmadina, Ferona Puan; Diar, Nining Fuji; Febrina, Sofhia Aldira; Apitalia, Sri; Ikhlas, Maula Fatihal (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Waste is one of the problems often faced in society. Most of the waste produced comes from household waste. One effort to deal with this problem is to process waste into agricultural products such as fertilizer. This activity aims to introduce the correct technique for making liquid organic fertilizer to the public from household waste. The method used is socialization and training in making liquid organic fertilizer. The practices that have been carried out regarding the socialization of making liquid organic fertilizer (POC) have provided new insight to the people of Perian Village that household organic waste can be used as fertilizer for agriculture.